MANAJEMEN PEMASARAN BERBASIS ONLINE BAGI USAHA RUMAHAN SUSU KEDELAI - Riski Nur Istiqomah Dinnullah (Universitas Muhammadiyah Ponorogo, 2019)
Soy milk is a beverage product made from soybeans in order to increase protein consumption. Soy milk has been widely known as alternative milk to cow's milk for people who are allergic and do not like cow's milk or for those who can not reach the price of cow milk is relatively expensive. Processing soybeans into good soy milk can create added value and the value of the product so that it can improve the development of UKM soy milk. Partners in this activity are Mr. Salim and Mrs. Farida Yati UKM’s are located in Kelurahan Bugul Lor, Panggung Rejo Subdistrict, Pasuruan City. In the home industry, marketing management is done only limited to the products that are entrusted by traveling traders, stalls and shops near the production site. Lack of marketing management is certainly caused less widespread area of product marketing. Therefore, an online marketing management is required. Through the utilization of social media, in addition to expanding the marketing area, people can recognize the soy milk produced by the UKMs.